Kebijakan Formulasi Jual Beli Aset Kripto yang Melibatkan Notaris dalam Mencegah Tindak Pidana Pencucian Uang - Ido Gustiawan Putra; M. Arief Amrullah; Firman Floranta Adonara (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The rapid development of crypto assets characterized by decentralization, anonymity, and high transaction speed has increased the risk of money laundering, which is not yet fully addressed by Indonesia’s current legal framework. This study aims to analyze the ratio legis of the existing regulatory formulation concerning crypto asset transactions involving Notaries in preventing money laundering and to propose an ius constituendum to strengthen future legal protection. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. The findings indicate that Indonesia’s regulations cover economic aspects and AML measures, however the preventive framework remains sectoral because AML obligations are imposed only on crypto asset traders, resulting in an incomplete preventive protection mechanism. The discussion highlights that involving Notaries as authentic deed officials has the potential to reinforce due diligence, enhance legal certainty, and prevent the misuse of crypto assets for money laundering in accordance with FATF standards. The study concludes that revisions to the Financial Sector Development and Strengthening Law, the Anti-Money Laundering Law, and related regulations are necessary to mandate Notary involvement in every crypto asset transaction as part of a national AML strategy.